Pre-Service English Teachers’ Perceptions Towards the Implementation of Differentiated Instruction in Teaching Practicum : Challenges and Strategies - Farah Maulida Afanin; Arik Susanti (International Journal of Multilingual Education and Applied Linguistics, 2025)
This study also highlights the importance of ongoing professional development for pre-service teachers, emphasizing that preparation for handling diverse classroom needs is crucial for effective DI implementation. Pre-service teachers identified the need for more targeted training in understanding students' individual learning styles and needs, especially when dealing with large classrooms and limited resources. The findings also suggest that collaborative learning among educators, through workshops and peer mentoring, plays a significant role in overcoming the challenges of DI. In addition, institutional support was identified as a key factor in facilitating the effective use of DI. Participants reported that a lack of resources, such as teaching aids and time, was a primary barrier to the full implementation of DI. Schools and educational institutions were urged to provide more resources and structured support systems to enable teachers to tailor their teaching methods to accommodate the varying abilities of their students. Furthermore, the integration of technology was highlighted as an effective strategy to differentiate instruction, allowing teachers to cater to diverse learning needs in a more flexible and engaging manner. For instance, digital tools such as learning management systems and interactive applications were utilized by some participants to create personalized learning paths for students, fostering both engagement and motivation. These strategies not only helped overcome some of the limitations faced by the teachers but also allowed students to engage more actively with the learning material. Ultimately, this study emphasizes that the successful implementation of Differentiated Instruction requires a collaborative effort between pre-service teachers, their educational institutions, and ongoing support systems.